2021
DOI: 10.3389/fenvs.2021.630668
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation in Microbial Community in Response to As and Pb Contamination in Paddy Soils Near a Pb-Zn Mining Site

Abstract: Mining activity is a growing environmental concern as it contributes to heavy metals (HMs) pollution in agricultural soils. Microbial communities play an important role in the biogeochemical cycling of HMs and have the potential to be used as bioindicators. Arsenic (As) and lead (Pb) are the most hazardous HMs and are mainly originated from mining activities. However, spatial variation in microbial community in response to As and Pb contamination in paddy soils remains overlooked. In this study, the biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 91 publications
1
3
0
Order By: Relevance
“…Several studies have shown that low As pollution (<20 mg kg −1 ) in paddy soils can negatively influence microbial community structure and reduce bacterial diversity and abundance (Chakraborty & Islam, 2018; Sheik et al, 2012). Regression analysis showed that high concentrations of As (up to 262 mg kg −1 ) had negative effects on soil bacterial diversity in rice ecosystems (Figure 2A, Figure S1), which is consistent with the findings of previous studies (Zou et al, 2021). Although the As‐detoxification genes, such as aoxB, arxA, and arsM, were ubiquitous in soil (Zhang et al, 2015; Zhang et al, 2021), As‐detoxification gene diversity (Shannon index) was low in the low‐As (from 9.76 to 19.74 mg kg −1 ) continental paddy soils (Zhang et al, 2021), reflecting the limited capacity of microbes to resist As contamination.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that low As pollution (<20 mg kg −1 ) in paddy soils can negatively influence microbial community structure and reduce bacterial diversity and abundance (Chakraborty & Islam, 2018; Sheik et al, 2012). Regression analysis showed that high concentrations of As (up to 262 mg kg −1 ) had negative effects on soil bacterial diversity in rice ecosystems (Figure 2A, Figure S1), which is consistent with the findings of previous studies (Zou et al, 2021). Although the As‐detoxification genes, such as aoxB, arxA, and arsM, were ubiquitous in soil (Zhang et al, 2015; Zhang et al, 2021), As‐detoxification gene diversity (Shannon index) was low in the low‐As (from 9.76 to 19.74 mg kg −1 ) continental paddy soils (Zhang et al, 2021), reflecting the limited capacity of microbes to resist As contamination.…”
Section: Discussionsupporting
confidence: 91%
“…Approximate 50 g rhizosphere and non-rhizosphere sediments in pond 1, ditch, and pond 2 of these two systems were also collected at days 15, 30, and 60, representing the early, middle, and late stages of the experiment, respectively (Zou et al, 2021). About 10 g of fresh sediment samples was used to measure water contents (WC) of each sediment sample gravimetrically.…”
Section: Analysis Of Water and Sedimentsmentioning
confidence: 99%
“…In contrast, the higher relative abundances of Bacteroidota near operating mines suggest that these landscapes could provide favorable conditions for some microorganisms. Bacteroidota usually harbor the majority of heavy metal resistance genes ( Yan et al, 2020 ), and is able to quickly adapt and endure high heavy metal stresses in mining polluted areas ( Zhao et al, 2020a , b ; Zou et al, 2021 ). Characterizing soil properties, assessing dust emissions from mines, and measuring heavy metal concentrations in mosses would be important next steps to further identify the environmental drivers responsible for changes in phyllosphere community structure observed in mine offsite landscapes.…”
Section: Discussionmentioning
confidence: 99%